1998
DOI: 10.1111/j.1751-1097.1998.tb05287.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescence of Horseradish Peroxidase and Acetaldehyde Related with Gallic Acid and Hydrogen Peroxide Interaction

Abstract: Abstract— This study focuses on the fact that the chemiluminescence in the visible region is emitted from the H2O2/gallic acid/ horseradish peroxidase (HRP) and the H2O2/gallic acid acetaldehyde (MeCHO) systems. The concentration dependence of chemiluminescence intensity that led to the different response of HRP and MeCHO toward H2O2 indicates that the photon emission participates with peroxidase activity including an electron transfer reaction. From our experimental results, in this study, we postulated a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Cholic acids produced light emission in the presence of H 2 O 2 and gallic acid, same as soyasaponin β g. Figure 2 shows the photon emission observed from the H 2 O 2 /cholic acids, H 2 O 2 /gallic acid/cholic acids and H 2 O 2 /cholic acids/CH 3 CHO systems using a CCD camera. We have previously shown, through the chemiluminescence method, that gallic acid and CH 3 CHO are typically Y and Z, respectively, in the XYZ chemiluminescence system [5,6]. Photon properties of cholic acids suggest that cholic acids act as Z in the XYZ system.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Cholic acids produced light emission in the presence of H 2 O 2 and gallic acid, same as soyasaponin β g. Figure 2 shows the photon emission observed from the H 2 O 2 /cholic acids, H 2 O 2 /gallic acid/cholic acids and H 2 O 2 /cholic acids/CH 3 CHO systems using a CCD camera. We have previously shown, through the chemiluminescence method, that gallic acid and CH 3 CHO are typically Y and Z, respectively, in the XYZ chemiluminescence system [5,6]. Photon properties of cholic acids suggest that cholic acids act as Z in the XYZ system.…”
Section: Resultsmentioning
confidence: 98%
“…Previously, we proposed that the reactive oxygen species/hydrogen donor/mediator system (XYZ system) was a new chemiluminescence system for the measurement of reactive oxygen scavenging activity [5,6]. This chemiluminescence system suggests that the two species of a hydrogen donor (Y) and a mediator (Z) are important and necessary to complete the elimination of a reactive oxygen species (X) through light energy transformation.…”
Section: Introductionmentioning
confidence: 99%
“…However, our previous study demonstrated a low-level chemiluminescence from the H 2 O 2 /gallic acid/hemoprotein, suggesting that this chemiluminescence arose from excited triplet carbonyls through the peroxidase-like activity of hemoprotein (11)(12)(13). The combination of gallic acid and hemoprotein, which are chemiluminescence agents in this system, showed synergistic activity to the hydroxyl radical and O 2 Ϫ inhibitions and antioxidative effect (11)(12)(13). Therefore, we hypothesized the H 2 O 2 -scavenging pathway to explain the mechanism of the hemoprotein chemiluminescence.…”
Section: Introductionmentioning
confidence: 83%
“…5B. We have reported the molar ratio of H 2 O 2 /horseradish peroxidase (HRP) (63:1) from the chemiluminescence experiment using the H 2 O 2 /gallic acid/HRP system (12). The consumption ratio of H 2 O 2 could be determined from the photon rate-determining step when using the same hydrogen donor.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that low-level chemiluminescence arose from the H 2 O 2 /flavonoid/ acetaldehyde system (11,12). This chemiluminescence can be observed by mixing three species a reactive oxygen species (X), a hydrogen donor (Y) and a mediator (Z) at room temperature and under neutral conditions (13). In addition, photon intensity (P) in this system, shows high concentration dependence on X, Y and Z, as indicated in the equation (14).…”
Section: Introductionmentioning
confidence: 99%